2004
DOI: 10.1530/eje.0.151u089
|View full text |Cite
|
Sign up to set email alerts
|

Application of gonadotropin releasing hormone in hypogonadotropic hypogonadism--diagnostic and therapeutic aspects

Abstract: Background: Puberty is the result of reactivation of the gonadotropin releasing hormone (GnRH) pulse generator resulting in an increasing release of GnRH by the hypothalamus, which stimulates the gonadotropic cells of the pituitary to synthesize and secrete LH and FSH. Hypogonadotropic hypogonadism (HH) is often the result of GnRH deficiency. The clinical picture is characterized by the absence of pubertal development and infertility. It is difficult to differentiate HH from delayed puberty since low gonadotro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
1
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(21 citation statements)
references
References 15 publications
1
18
1
1
Order By: Relevance
“…hCG is a clinically used growth factor in the treatment of delayed puberty in adolescents (Delemarre-van de Waal, 2004;Soliman et al, 2005). Previous in vitro studies using hCG have demonstrated that this growth factor can radiosensitize mammary carcinoma cells, although no mechanistic analyses as to the mode of cell killing were performed (PondTor et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…hCG is a clinically used growth factor in the treatment of delayed puberty in adolescents (Delemarre-van de Waal, 2004;Soliman et al, 2005). Previous in vitro studies using hCG have demonstrated that this growth factor can radiosensitize mammary carcinoma cells, although no mechanistic analyses as to the mode of cell killing were performed (PondTor et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…The pulsatile nature of this secretion is critical for the testicular response and spermatogenesis [3,[15][16][17]. Continuous chronic administration of GnRH induces secondary infertility due to loss of this pulsatile secretion [18,19].…”
Section: Discussionmentioning
confidence: 99%
“…The management of male infertility in cases of HH is complex due to the difficulty in imitating the normal physiological secretion of gonadotropins [1,14]. While using GnRH-injecting pumps is one technique in which GnRH is injected subcutaneously in a pulsatile nature [14,15], the availability and expertise with these pumps are limited to a few specialized centers [1,13]. Furthermore, the success rate with this relatively cumbersome method is moderate [1,12].…”
Section: Discussionmentioning
confidence: 99%
“…However, the response of gonadotropins to an acute challenge of GnRH can be difficult to interpret, since in the pre-pubertal state the pituitary, although intact, will not or hardly respond, similar to the situation in hypogonadotropic hypogonadism (7). Repetitive administration of GnRH intravenously does increase gonadotropin levels in patients in a pre-pubertal and hypogonadotropic state.…”
Section: Introductionmentioning
confidence: 99%